Design requirements of Sustainable passengers’ - Khalil Ibrahim Ali; Mohammed Saad Al-Jorani (Iraqi Journal of Architecture and Planning, 2018)
Public transport stations and terminals are considered as a core to achieve sustainable development in society which needs linking of various transportation modes in an unified place to create an interaction between passengers and the facilities there in most developed counties had witnessed an increasing attention to encourage such interaction in public transport facilities. Sustainability has become an influential factor in the design of these facilities. Approaches to sustainable design have become increasingly important. This paper presents useful guidelines to the designer of these facilities with focal concern to sustainable factors that needs to be adhered to in the design. The paper reviews various studies and recent literature relevant to the design and links available know how to sustainable requirements. It defines the problem as '' the required needs for designers to understand the needs for sustainable design for public transport facilities". Based on this it suggests a hypothesis that indicates sustainable design will increase interaction between users and the building facilitating transport modes. From the literature, a theoretical frame work was achieved with significant relation to sustainability. Reviewing existing facilities of transportation buildings in developed countries through this frame work has guided the research to reach a set of findings which could assist in the design of such facilities thus the problem is given a direction to solve and assist in the design.Keywords: sustainable transportation system, sustainable passengers 'land-transportations stations.